"I know! I live here": poor women and the work of empowerment. Issue 7 (3rd October 2017) - Dhanju, Richa; O'Reilly, Kathleen
ABSTRACT: To trace the effects of empowerment programmes in the Global South, attention needs to be focused on the everyday practices of frontline staff, or fieldworkers, who convey empowerment ideas and practices at the grassroots. This is especially critical when fieldworkers work in the marginalised communities where they also live. Instead of looking outward towards a programme's outcomes, this article turns inward to examine the impact of women fieldworkers' dual experiences of development on their decisions and practices in the field. The ethnography of women fieldworkers in a government-led women's empowerment programme for the poor in Delhi, India reveals the uneasy relationship of women's empowerment to the larger contradictory development paradigm that they work within. Fieldworkers used their experiences as poor women to meet programme quotas, while also side-lining social change in favour of shielding clients from ineffective programme activities.